Character Design in Indonesian Animated Series: Escaping The Shadow of Foreign Hegemony - Dominika Anggraeni Purwaningsih (ULTIMART Jurnal Komunikasi Visual, 2016)
Whilst animated series, whether it’s a TV series or web series is a relatively new media in Indonesia, it has gone through a significant process. One of the interesting aspects that we can observe from it is the development of the character design. It’s undeniable that foreign hegemony contributed in major parts of the design but we can’t overlook the efforts in finding Indonesia’s very own unique character design and how it affects the successors. This paper will study the character designs of Indonesia animated series from the earliest known to the latest to date when this paper is written. The method used is comparative descriptive case study, the research focus is the design character of contemporary Indonesian animation and then compared with foreign animation character design, in this study primarily is animation of Japan and the United States as the dominant power in both areas. By conducting case studies, this study aimed to develop in-depth analysis of the subject matter of the character designs in terms of aspects that enrich the visual and qualitative approach. Keywords: character design, Indonesia animation, animated web series, animated TV series